Competitiveness in the textile and clothing supply chain - Hussain, Deedar (2011)
The competitiveness scenario in the textile and clothing is always changing with the entrance of new players and changes in the rules of trade. This can be observed by looking at the developments that took place around the world in the last decade. This study finds how things are changing in this chain and how players are positioning themselves in this new competitive scenario. One such player of the chain is focused for study and its strategic position was analyzed and directions for improving competitiveness were identified. The focus is taken to more depth by considering the tactical issues for the competitive options already identified.